COMPARISON OF TRANSFORAMINAL LUMBAR INTERBODY FUSION AND POSTERIOR LUMBAR INTERBODY FUSION IN THE MANAGEMENT OF SINGLE-LEVEL LUMBAR SPONDYLOLISTHESIS - KHATTAK , SN; REHMAN , S; ANWER , MS; SAEED , K; RAHIM , IU (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to compare the outcomes of transforaminal lumbar interbody fusion and posterior lumbar interbody fusion in managing single-level lumbar spondylolisthesis. A Randomized Controlled trial was conducted at the Department of Neurosurgery, Gomal Medical College, DI Khan, Pakistan, from December 2022 to May 2023 on 50 patients presenting with adult lumbar spondylolisthesis. In group A, 25 patients underwent posterior lumbar interbody fusion (PLIF) utilizing two cages and pedicle fixation, while 25 patients received transforaminal lumbar interbody fusion (TLIF) employing a single cage and pedicle fixation, representing group B. Outcomes such as mean operative times, blood loss, back and leg pain score on VAS, and complications were assessed between both groups. The mean postoperative time, blood loss, and back pain on the VAS scale were significantly lower in the TLIF group than in the PLIF group. The TLIP group showed a lower number of complications as compared to the PLIF group. TLIF outperforms PLIF regarding functional outcomes and the rate of complications for grade I/II single-level lumbar spondylolisthesis.